TODDLER ENGLISH CLUB: Pembelajaran Bahasa Inggris Anak Usia Dini di Kampung Sindang Sari, Bogor - Istiqlaliah Nurul Hidayati; Aqh Mazia Al-Islami; Siti Meri Andiani; Yasinta Listiani; Irfan Maulana (LPPM Universitas Islam 45 Bekasi, 2022)
Toddler English Club is a community service program carried out in the context of the academic community's concern for the development of early childhood intelligence. In Education, Early Childhood is a child who is in a golden age with a level of potential development. Ability in language encourages children to be more adaptive, more intellectually, linguistically, socially, and academically. Sindang Sari Village, which is located in Bojongrangkas Village, Ciampea District, Bogor Regency, is the location for the Pakuan University Real Work Lecture. he partner in this service is PAUD Kania which has provided special support in the implementation of the Toddler English Club program with training methods for its students. The Toddler English Club training is carried out very dynamically, this is evidenced by the activeness and responsiveness of the students, this is due to the excavation and disclosure of information from PAUD Facilitator Teachers as well as their involvement in this training..